Aquilaria sinensis essential oil inhibits biofilm formation and virulence of Staphylococcus aureus - Wang, Fang; Ding, Zhi-Wen; Wang, Ying-Jie; Xu, Kai-Zhong; Dar, Owias Iqbal; Wang, Min; Sethupathy, Sivasamy; Liu, Yang-Yang; Tang, Shi (Frontiers in Microbiology, 2025)
Staphylococcus aureus is a major foodborne pathogen characterized by strong virulence and biofilm-forming ability, posing a persistent threat to food safety. Aquilaria sinensis (Lour.) Gilg, a medicinal and edible plant found in tropical regions such as Hainan, has rarely been investigated for its quorum-sensing inhibitory (QSI) potential. In this study, four types of A. sinensis essential oils were systematically evaluated for their ability to inhibit quorum sensing and related virulence in S. aureus. Among them, the Tong-Ti-Xiang type supercritical essential oil (TTC) exhibited the strongest activity. At a sub-inhibitory concentration of 125 μg/mL (1/4 MIC), TTC reduced biofilm formation by up to 78% without affecting bacterial growth. Confocal laser scanning Microscopy and scanning electron microscopy analyses further confirmed that TTC compromised the density and structural integrity of the biofilms. Moreover, TTC suppressed α-hemolysin activity and significantly downregulated quorum-sensing-regulated genes involved in biofilm formation and adhesion, including icaA, icaD, clfA, clfB, and agrA. Gas chromatography mass spectrometry analysis revealed that TTC is rich in chromone derivatives, among which 2-phenethyl-4H-chromen-4-one showed strong binding affinity toward the adhesion-associated IcaA protein and the QS-associated AgrA protein in molecular docking analysis, suggesting it as a key active compound responsible for the observed QSI effect. Overall, these findings highlight TTC as a promising natural anti-biofilm and anti-virulence agent for controlling foodborne pathogens.